2013
DOI: 10.1177/1550059412475066
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Entropy Analysis of Electroencephalography During Sleep in Patients With Parkinson Disease

Abstract: Sleep disorders are frequently seen in patients with Parkinson disease (PD), including rapid eye movement (REM) behavior disorder and periodic limb movement disorder. However, knowledge about changes in non-REM sleep in patients with PD is limited. This study explored the characteristics of electroencephalography (EEG) during sleep in patients with PD and non-PD controls. We further conducted multiscale entropy (MSE) analysis to evaluate and compare the complexity of sleep EEG for the 2 groups. There were 9 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
4
37
0
1
Order By: Relevance
“…In addition, in comparison with other non-invasive brain imaging approaches, EEG irregularity and complexity analyses have been successfully and widely employed and provide a new view to understand physiological processes in both healthy and pathological conditions in AD [1,11,13,[26][27][28]. The MSE-and mvMSE-based methods have been successfully used to characterise biomedical signals to detect different pathological states like epilepsy, schizophrenia, Parkinson's disease, and AD [13,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in comparison with other non-invasive brain imaging approaches, EEG irregularity and complexity analyses have been successfully and widely employed and provide a new view to understand physiological processes in both healthy and pathological conditions in AD [1,11,13,[26][27][28]. The MSE-and mvMSE-based methods have been successfully used to characterise biomedical signals to detect different pathological states like epilepsy, schizophrenia, Parkinson's disease, and AD [13,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[4] used MSE for determining automatic sleep score by analyzing EEG data from C3-A2 channel. Using MSE on sleep EEG of Parkinson patients, Chung et al [5] have found that the complexity of EEG was significantly distinguishable between normal group and Parkinson patients at higher time scale for central electrodes.…”
Section: Introductionmentioning
confidence: 98%
“…Multiscale entropy (MSE), a nonlinear analysis measure, has been applied to a variety of biomedical signals [9][10][11][12]. Costa et al firstly proposed and employed MSE to biomedical signals analysis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al firstly proposed and employed MSE to biomedical signals analysis [9,10]. Chung et al analysed the electroencephalography (EEG) during sleep in patients with Parkinson's disease using MSE [11]. Zhang et al employed MSE to analyse characterizing different patterns of spontaneous electromyogram (EMG) signals [12] and then got the nonlinear features of these patterns.…”
Section: Introductionmentioning
confidence: 99%